Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan dan Persepsi Risiko Terhadap Minat Menggunakan Shopee Paylater - Winda Suciani Siregar; Annio Indah Lestari Nasution; Nurwani Nurwani (CV. Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of Perceived Benefit, Perceived Ease of Use and Perceived Risk on Interest in Using Shopee Paylater in Students of the Islamic Economics and Business Faculty of UIN North Sumatra, either partially or simultaneously. The method used in this research is a quantitative method. The population of this study was conducted on students of the Faculty of Economics and Islamic Business at UIN North Sumatra with a sample of 100 students. Using primary data by distributing questionnaires and multiple regression analysis method using hypothesis testing. The results of this study partially show that Perceived benefits, Perceived Ease of Use and Perceived Risk have a positive and significant effect on the interest in using Shopee Paylater among students of the Islamic economics and business faculty of UIN Sumatra Utara. Then simultaneously Perceived Benefits, Perceived Ease of Use and Perceived Risk influence the interest in using Shopee Paylater for Students of the Faculty of Islamic Economics and Business, UIN North Sumatra